La dramatización para estimular la creatividad en los niños de primero de básica paralelo a y b de la unidad educativa Fernando Daquilema, de la ciudad de Riobamba, provincia de Chimborazo año lectivo 2014 – 2015 - Casco Daquilema, Elvia Yolanda (2016)
This research; It was a treaty of great importance to education. In conducting the study of the problem. How dramatization stimulates creativity in children of first parallel A and B basic educational unit Daquilema Fernando, City of Riobamba, province of Chimborazo school year 2014 - 2015? He was raised as a general goal, determine how the drama stimulates creativity in children, three specific objectives outlined; diagnose application dramatization, analyze the level of creativity and propose solutions. Based on the study and analysis of the theoretical framework. It stipulated that social and emotional skills developed through drama strengthen the development of creativity and optimize the integral formation. Creativity is the generation of new ideas, the ability to create or invent original solutions to various problems to face reality. The methodology used to facilitate the investigation was explanatory causal type by using observation and interview, and correlates descriptive applied using inductive and deductive method. To collect observation data with their respective learning process tab is applied. An interview with a guide to collect information from teachers went. It get the conclusion that the dramatization, does influence significantly in stimulating creativity verifying that the hypothesis is true.